Source Impact Determination using Airborne and Ground Measurements of Industrial Plumes - Leoni, Cecilia; Hovorka, Jan; Dočekalová, Veronika; Cajthaml, Tomáš; Marvanová, Soňa (Environmental science & technology, 2016)
Industrial particulate matter (PM) air pollution exposing nearby residential areas forms several European air pollution hot-spots. One of these hot-spot is the residential district of Ostrava Radvanice-Bartovice with frequent exceedances for PM and benzo[a]pyrene B[a]P, a carcinogenic polycyclic aromatic hydrocarbon (PAH) of MW > 228 amu. Such PAHs are highly bonded to the ultrafine particles (UFPs), the smallest PM size fraction, which deposits most efficiently in the alveolar region of human lungs. Airborne measurements identified UFP point sources in the adjacent metallurgical complex and mapped limited horizontal and vertical dispersion of industrial plumes enriched with UFPs (3.2 × 10(5)cm(-3)). The plumes, episodes of simultaneous peaks of UFPs (1.4 × 10(5)cm(-3)), SO2 (88.2 ppb), and CO (11.3 ppm), were recorded on the ground downwind in the residential district when wind speeds >1 ms(-1). In the plumes, UFPs were mostly 19-44 nm in diameter, enriched with PAHs/B[a]P up to 43.8/3.5 mg·g(-1). Electron microscopy showed that these plume UFPs were mostly agglomerates of spherules of 30-50 nm in diameter. These source impact measurements, that combine airborne and ground-level measurements, are applicable to clearly identify specific industrial air pollution sources and provide information to assess their possible impact to human health in similar hot-spots worldwide.
Keywords: Particulate Matter; Wind; látky znečišťující vzduch; znečištění ovzduší; pevné částice; Humans; Metallurgy; lidé; vítr; Air Pollutants; hutnictví; Air Pollution